Основоположники арабо-мусульманской историографии (IX–начала X века) - Шагинян, Арсен
The culmination of the “Golden Age” of Islamic literary culture was the multivolume “History of the Prophets and Kings” (Ta’rīḫ ar-Rusul wa-l-Mulūk) by the “father of Muslim historiography”, an Arabic spoken Iranian Muḥammad b. Ǧarīr (Djarir) aṭ-Ṭabarī (839–923), which outlines the general history since the Creation, as well as the works of other founders of the Islamic historiography in Classical Arabic – al-Kūfī, Ḫalīfa b. Ḫayyāṭ (Khalifah b. Khayyat), ad- Dīnawarī, al-Balāḏurī (al-Beladsori), al-Ya‘qūbī (al-Ja‘qubi). The breakthrough works by these authors contain a lot of data concerning the countries and peoples of the Armenian Highlands, Caucasus, Asia Minor, and North-Western Iran (Atropatene-Azerbaijan), as well as adjacent areas of the Mesopotamia, Media, and Syria from Ancient times to the early of the 10th c. These materials may well be of interest to readers of the periodical “Studies in oriental sources” (Institute of Oriental Studies, National Academy of Sciences of the Republic of Armenia).
Keywords: Арабо-мусульманской историография